Peran pancasila dalam memperkuat identitas nasional bangsa indonesia - Rokhman, M. Lutfi Hidayatul (Maliki Interdisciplinary Journal, 2026)
Pancasila, as the foundation of the state, plays a crucial role in shaping and strengthening Indonesia’s national identity. Amid the rapid flow of globalization, which brings various foreign cultural influences, Pancasila serves as the main guideline in preserving national values, unity, and the nation’s identity. This paper aims to examine the role of Pancasila in reinforcing national identity by using a qualitative approach through a literature review from various sources, including news and academic journals. The results of the analysis show that the values contained in Pancasila, such as mutual cooperation, tolerance, and social justice, remain relevant in facing contemporary challenges, including social conflicts, threats of national disintegration, and moral crises. In addition, the implementation of Pancasila values in daily life is a key factor in maintaining national unity and integrity. Therefore, efforts to enhance the understanding and practice of Pancasila must continue to be strengthened through education and public policies so that national identity remains solid amid the dynamics of changing times.